Reog and Its Possession in Preserving Cultural Identity in Central Java, Indonesia - Putri, Stephanie Priyanto (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
This research aimed to show Reog and its possessions that may occur during the performance as a cultural heritage in Indonesia. Only a few people know what exactly happens which leads people to have misconception about this cultural identity. It seems to be a need to figure out about it. The research focused to show the real possession occurs including what the players do, see, and feel during the performance. This study was conducted in Pojoksari, Ambarawa, Central Java. The qualitative data was gained through interviews and observation while the questionnaire utilized was used for triangulating the data from interviews. The researcher constructed the questions for both interviews and questionnaire after the observations. The interview was conducted to the players, shaman, and the music players while the questionnaire was given to the remaining members. The result revealed that this group has never had made-up possessions. Besides, during the state of being possessed, the players tend to feel and see nothing and they usually move uncontrollably. After the performance, in fact, they feel dizzy and pain all over their body. Some requirements are fundamental to perform Reog safely such as shaman, players, music, and sesajen. This research is expected to bring contribution to other researchers to explore as no detail study was conducted on this related topic.